2020
DOI: 10.4103/digm.digm_22_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and mental health: A review and the role of telehealth and virtual reality

Abstract: On March 12, 2020, with more than 20,000 confirmed cases and almost 1000 deaths in the European Region, the World Health Organization classified the COVID-19 outbreak as a pandemic. As of August 15, 2020, there are 21.5 million confirmed cases of COVID-19 and over 766,000 deaths from the virus, worldwide. Most governments have imposed quarantine measures of varied degrees of strictness on their populations in attempts to stall the spread of the infection in their communities. However, the isolation may have in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…VR had various health usages during the pandemic including physical and cognitive rehabilitation, pain management, treatment of psychological disorders, and healthcare professional training [ 21 ]. Also, VR has the potential to facilitate remote therapies that can be more consistent, scalable, and available [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…VR had various health usages during the pandemic including physical and cognitive rehabilitation, pain management, treatment of psychological disorders, and healthcare professional training [ 21 ]. Also, VR has the potential to facilitate remote therapies that can be more consistent, scalable, and available [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies revealed the potential of digital therapeutic technology like as immersive VR that offer cost-effective, scalable, and on-demand solution to address mental problems. Since COVID-19 era has prolonged yet, VR intervention has the potential strength to minimize face-to-face intervention [ 22 ]. Despite the growing importance and necessity of distant-delivered treatment or non-directive treatment for psychiatric problems in this pandemic era, there has not been much research related to VR interventions for COVID-19-related psychological distress [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations